2020
DOI: 10.24018/ejmed.2020.2.3.262
|View full text |Cite
|
Sign up to set email alerts
|

Genetic And Environmental Factors Involved In The Development Of Oral Malformations Such As Cleft Lip/Palate In Non-Syndromic Patients And Open Bite Malocclusion

Abstract: Among the most common malformations observed in the oral cavity are cleft lip/palate and malocclusions, being this last one considered by the World Health Organization, the third public health problem.Malocclusions include the anterior open bite, a change in the vertical plane, that can be of two types: dental anterior open bite and skeletal anterior open bite. Cleft lip and cleft palate are the most common congenital malformations at birth. These malformations result from a failure in the normal craniofacial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Other studies have investigated genetic factors that contribute to the development of open bite, and have found that genes involved in the growth and development of bones, teeth, and soft tissues may be associated with this malocclusion [45]. Several genes have been identified, including CYP19A1, GHR, TNF-α, RANKL/RANK, OPG, MYO1H, MMP, TIMPs, α-actin, and PTHR1 [46]. However, environmental factors are also important, and the occurrence of open bite is multifactorial, resulting from the interaction of genetic and environmental factors.…”
Section: Findings Of Literature Searchmentioning
confidence: 99%
“…Other studies have investigated genetic factors that contribute to the development of open bite, and have found that genes involved in the growth and development of bones, teeth, and soft tissues may be associated with this malocclusion [45]. Several genes have been identified, including CYP19A1, GHR, TNF-α, RANKL/RANK, OPG, MYO1H, MMP, TIMPs, α-actin, and PTHR1 [46]. However, environmental factors are also important, and the occurrence of open bite is multifactorial, resulting from the interaction of genetic and environmental factors.…”
Section: Findings Of Literature Searchmentioning
confidence: 99%
“…AOB may impact aesthetic, phonetic, and psychological well-being [5]. As reported in the literature, several hereditary and environmental etiological factors are involved in anterior open bite malocclusion [5][6][7]. Extrinsic factors include non-nutritive sucking habits, abnormal tongue posture, specific dietary habits, mouth breathing (frequently associated with enlarged adenoids or tonsils), and all conditions directly related to altered orofacial growth [3,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Cleft lip and palate (CLP) disorders happen when the upper lip or hard palate does not form completely during fetal development, resulting in a gap or split in the lip/palate. This condition can affect either the hard palate or the soft palate due to incomplete fusion of the tissues that make up the palate (Leal et al, 2020;Vyas et al, 2020). Cleft lip disorder is a common birth abnormality that affects around 700 babies worldwide each year (Mc Goldrick et al, 2023;Muzammil et al, 2021).…”
Section: Introductionmentioning
confidence: 99%